2012
DOI: 10.1021/ie302390b
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Neural Networks, Optimization and Kinetic Modeling of Amoxicillin Degradation in Photo-Fenton Process Using Aluminum Pillared Montmorillonite-Supported Ferrioxalate Catalyst

Abstract: An artificial neural network (ANN) was applied to study the hierarchy of significance of process variables affecting the degradation of amoxicillin (AMX) in a heterogeneous photo-Fenton process. Catalyst and H2O2 dosages were found to be the most significant variables followed by degradation time and concentration of AMX. The significant variables were optimized and the optimum condition to achieve degradation of 97.87% of 40 ppm AMX was 21.54% excess H2O2 dosage, 2.24 g of catalyst in 10 min. A mathematical m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(21 citation statements)
references
References 27 publications
1
19
0
1
Order By: Relevance
“…9.24 for model Y and 8.84 for model Z). The Model F-value is 77.77 and 15.30 for the response function Y and Z, respectively, and these values implied that the models are significant and there is less than 0.01% probability that Model F-values this large could occur due to model error or noise, although it may be associated to experimental error [40][41][42].…”
Section: Regression Model Development and Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…9.24 for model Y and 8.84 for model Z). The Model F-value is 77.77 and 15.30 for the response function Y and Z, respectively, and these values implied that the models are significant and there is less than 0.01% probability that Model F-values this large could occur due to model error or noise, although it may be associated to experimental error [40][41][42].…”
Section: Regression Model Development and Analysismentioning
confidence: 99%
“…Similarly their adjusted regression coefficient, R 2 adj , that corrects regression coefficient, R 2 , based on the number of terms in the models and the sample size [41] are 0.9782 and 0.9548, respectively. Generally, if a model contains many terms and has small sample size this could result in a much lower R 2 adj compared to R 2 [40,41], in these cases the models have high R 2 and R 2 adj which indicated that the chosen quadratic model for response surface method (RSM) adequately describe the experimental data in the range of the operating parameters. Furthermore, the ''Pred R-Squared'' of 0.8511 and 0.8325 are in reasonable agreement with the ''Adj RSquared'' of 0.9782 and 0.9548 for the HDO and ISO models, respectively.…”
Section: Regression Model Development and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Basri et al also found that, for optimizing the lipase-catalyzed synthesis of a palm-based wax ester, ANN superiorly outperformed RSM [58]. More comparative studies using RSM and ANN can be found in References [59][60][61][62][63][64][65].…”
Section: Prediction Of Reaction Descriptorsmentioning
confidence: 99%
“…Fenton (H 2 O 2 and Fe 2þ ) and the related processes are easy-to-handle AOPs that have been used for antibiotic wastewater treatment (Ayodele et al, 2012;Elmolla and Chaudhuri, 2009a;Elmolla et al, 2010;Trov o et al, 2011). For instance, Elmolla and Chaudhuri (2009b) treated amoxicillin solution with Fenton reagent and a complete degradation of amoxicillin in 2 min and 81.4% of COD removal in 10 min were attained.…”
Section: Introductionmentioning
confidence: 99%